Developments in surface contamination and cleaning. Volume 7, - Kohli, Rajiv, 1947-; Mittal, K. L., 1945- (Elsevier, 2015)
As device sizes in the semiconductor industries are shrinking, they become more vulnerable to smaller contaminant particles, and most conventional cleaning techniques employed in the industry are not as effective at smaller scales. The book series Developments in Surface Contamination and Cleaning as a whole provides an excellent source of information on these alternative cleaning techniques as well as methods for characterization and validation of surface contamination. Each volume has a particular topical focus, covering the key techniques and recent developments in the area. The chapters in this Volume address the sources of surface contaminants and various methods for their collection and characterization, as well as methods for cleanliness validation. Regulatory aspects of cleaning are also covered. The collection of topics in this book is unique and complements other volumes in this series. Edited by the leading experts in small-scale particle surface contamination, cleaning and cleaning control, these books will be an invaluable reference for researchers and engineers in R & D, manufacturing, quality control and procurement specification situated in a multitude of industries such as: aerospace, automotive, biomedical, defense, energy, manufacturing, microelectronics, optics and xerography.